Modelling and application for eclampsia with SimMom. (2017) - Wang, Xue; Pan, Ying; Song, Liyou; Huang, Xiaochen; Liu, Ming; Liu, Anqi
In this paper, the issue of simulation-based education with SimMon is dealt with for training of the students and young doctors in obstetrics and gynaecology in the case of eclampsia in hypertensive disorders during pregnancy, together with the reasonable and standard drug treatment. The model is built and the practical training results are analysed and compared for the performance of two groups of students under model-based training and conventional training, respectively. The results show that there was no significant difference in the theoretical knowledge test and crossover test for the two groups of students, whereas practice test scores increased significantly (p < 0.05), with the group using the model of SimMom scoring higher than the other group. It proves that the SimMom application in obstetrics eclampsia will help to improve the clinical skills of medical students and young doctors. The advanced product makes a great contribution to reducing medical accidents, improving medicinal level and doctor-patient relationship, and promoting medical education.